2012
DOI: 10.1105/tpc.112.096248
|View full text |Cite
|
Sign up to set email alerts
|

A Transit Peptide–Like Sorting Signal at the C Terminus Directs the Bienertia sinuspersici Preprotein Receptor Toc159 to the Chloroplast Outer Membrane

Abstract: Although Toc159 is known to be one of the key GTPase receptors for selective recognition of chloroplast preproteins, the mechanism for its targeting to the chloroplast surface remains unclear. To compare the targeting of these GTPase receptors, we identified two Toc159 isoforms and a Toc34 from Bienertia sinuspersici, a single-cell C 4 species with dimorphic chloroplasts in individual chlorenchyma cells. Fluorescent protein tagging and immunogold studies revealed that the localization patterns of Toc159 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 77 publications
3
38
0
Order By: Relevance
“…5D, compare lanes 2-4 with 5). Control outer envelope protein, TOC159 (translocon at the outer envelope membrane of chloroplasts, 159 kDa), is known to have an intrinsically thermolysin-resistant portion (77)(78)(79). The resistant 52-kDa fragment was detected when thermolysin was present (Fig.…”
Section: Sfr2 Structural Modeling As a Framework For Understanding Sumentioning
confidence: 99%
“…5D, compare lanes 2-4 with 5). Control outer envelope protein, TOC159 (translocon at the outer envelope membrane of chloroplasts, 159 kDa), is known to have an intrinsically thermolysin-resistant portion (77)(78)(79). The resistant 52-kDa fragment was detected when thermolysin was present (Fig.…”
Section: Sfr2 Structural Modeling As a Framework For Understanding Sumentioning
confidence: 99%
“…In Bienertia, subcellular localization of the main TOC receptors TOC159/132 and TOC34 has been tested previously by in vivo localization studies. However, no preferential accumulation of the fusion constructs in either P- or C-chloroplasts was observed33. Therefore, there is currently no evidence for the involvement of these major TOC complexes in the differential sorting process.…”
Section: Discussionmentioning
confidence: 97%
“…However, it was later shown that the situation is a little more complex in that different substrates are imported with different efficiencies in chloroplasts of different development stages51. Also in Bienertia, levels of TOC 159 and TOC132 decrease from a very high level in young developing cells to a basal level towards leaf maturation33. Accordingly, either TOC composition or the sorting/import capacity in mature Bienertia protoplasts might be inadequate, especially when fusion constructs are massively overexpressed under the control of the 35 S promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The following protocol was adapted from Smith et al (2003), Yoo et al (2007), and Lung and Chuong (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, protoplasts to be used for transfection experiments should be resuspended in stabilization buffer to a final concentration of 200,000 protoplasts/mL (Lung and Chuong 2012).…”
mentioning
confidence: 99%